Management of benign paediatric thyroid nodules: experience from paediatric ENT services of a tertiary care hospital - Chakravarti, Arunabha; Chandrasekhar, Sneha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Thyroid nodules are a common occurrence in adults but are rarely seen in children. We present here four cases of paediatric thyroid nodules. Patients were subjected to a thorough clinical evaluation, blood thyroid level testing, ultrasonography (USG) and fine needle aspiration cytology (FNAC). The size of the nodules ranged from 2 cm to 7.5 cm. All four nodules were reported as “benign” on FNAC, of which three under-went total thyroidectomy owing to the bi-laterality and large size of the nodules. None of the cases had post-operative complications of hypocalcemia or recurrent laryngeal nerve paralysis. Of the 3 patients taken up for surgery one patient was found to have papillary thyroid carcinoma. Subsequent radiological investigation showed no residual disease. All three operated cases were followed-up in the ENT outpatient department for at least 2 years and showed no signs of recurrence. One patient with a small thyroid nodule (2 cm) was managed non – surgically and has been kept on follow up since 12 months. In our experience, total thyroidectomy, even in a benign disease, in expert hands, is a safe procedure and the best management option in children with large goiter, to avoid recurrence and thereby a redo surgery.